ROLE OF CRISPR TO IMPROVE ABIOTIC STRESS TOLERANCE IN CROP PLANTS - Farooq, MU; Bashir, MF; Khan, MUS; Iqbal, B; Ali, Q (Biological and Clinical Sciences Research Journal, 2021)
The study for genetic variation in plant genomes for a variety of crops, as well as developments of genome editing techniques, have made it possible to cultivate for about any desired trait. Zinc finger enzymes; have made strides in genome-editing. Molecular biologists can now more specifically target every gene using transcription activator-like effector nucleases and ZFNs. These methods, on the other hand, are expensive and time-consuming because they involve complex procedures. Referring to various genome editing techniques, CRISPR/Cas9 genetic modification is simple to construct and clone and the Cas9 could be used with different guide RNAs controlling different genes. Following solid evidence demonstrations using the main CRISPR-Cas9 unit in field crops, multiple updated Cas9 cassettes are often used in plant species to improve target precision and reduce off target cleavage. Nmcas9, Sacas9, as well as Stcas9 are a few examples. Furthermore, Cas9 enzymes are readily available from a variety of sources. Bacteria that had never been discovered before has found solutions available to improve specificity and efficacy of gene editing techniques. The choices are summarized in this analysis to plant’s experiment to develop crops using CRISPR/Cas9 technology; the tolerance of biotic & abiotic stress may be improved. These strategies will lead to the growth of non-genetically engineered crops with the target phenotype, which will further improve yield capacity under biotic & abiotic stress environments.